Anatomical and biological considerations to determine resectability in pancreatic cancer - Rompen, Ingmar F.; Habib, Joseph R.; Wolfgang, Christopher L.; Javed, Ammar A. (Cancers, 2024)
Pancreatic ductal adenocarcinoma (PDAC) remains associated with poor outcomes with a 5-year survival of 12% across all stages of the disease. These poor outcomes are driven by a delay in diagnosis and an early propensity for systemic dissemination of the disease. Recently, aggressive surgical approaches involving complex vascular resections and reconstructions have become more common, thus allowing more locally advanced tumors to be resected. Unfortunately, however, even after the completion of surgery and systemic therapy, approximately 40% of patients experience early recurrence of disease. To determine resectability, many institutions utilize anatomical staging systems based on the presence and extent of vascular involvement of major abdominal vessels around the pancreas. However, these classification systems are based on anatomical considerations only and do not factor in the burden of systemic disease. By integrating the biological criteria, we possibly could avoid futile resections often associated with significant morbidity. Especially patients with anatomically resectable disease who have a heavy burden of radiologically undetected systemic disease most likely do not derive a survival benefit from resection. On the contrary, we could offer complex resections to those who have locally advanced or oligometastatic disease but have favorable systemic biology and are most likely to benefit from resection. This review summarizes the current literature on defining anatomical and biological resectability in patients with pancreatic cancer.
Gesehen am 07.06.2024